Detrimental effects of intimate partner violence on the nutritional status of children: insights from PDHS 2012-2013 - Shaukat, Natasha; Iqbal, Meesha; Khan, Muhammad Arslan (International Journal Of Community Medicine And Public Health, 2018)
Background: Endemicity of intimate partner violence (IPV) against women is established globally. Children are directly dependent on mothers for care and nourishment. Literature has shown inconsistent association between IPV and nutritional status of children, and no nationwide study has been conducted in Pakistan to test this association. Thus, we aimed to do a secondary data analysis on Pakistan Demographic Health Survey (PDHS 2012-13) to explore the association of IPV and the nutritional status of children. Methods: This secondary data analysis was conducted on nationally representative data of PDHS 2012-13. All four provinces, including Islamabad Capital Territory and Gilgit Baltistan districts were taken, and two stage stratified random sampling was performed. The conflict tactics scale (CTS) was used to quantify Intimate Partner Violence (IPV), and its emotional and physical dimensions. Results: This study included mother-child dyads (n=1851) who completed the domestic violence module in PDHS. The lifetime prevalence of intimate partner violence was almost 40% among married women of reproductive age group. About 20% of women reported emotional violence and 2.5% women reported physical violence only. However, 16% of the women reported having suffered from both emotional and physical violence. Women who suffered from emotional violence had children with significantly higher odds of being underweight (OR, 95% CI: 1.57, 1.04-2.36) and stunted (OR, 95% CI: 1.54, 1.05-2.24) respectively. IPV was not found to be significantly associated with occurrence of wasting in children. Conclusions: Policy implications towards this issue call for establishing programmes and laws to protect women and children from the detrimental effects of violence. Provision of initiatives which focus on women autonomy and empowerment via increased access to education and economic opportunities.